2016
DOI: 10.1093/nar/gkw759
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based high-throughput compound screening reveals functional interaction between oncofetal HMGA2 and topoisomerase I

Abstract: HMGA2 is an important chromatin factor that interacts with DNA via three AT-hook domains, thereby regulating chromatin architecture and transcription during embryonic and fetal development. The protein is absent from differentiated somatic cells, but aberrantly re-expressed in most aggressive human neoplasias where it is causally linked to cell transformation and metastasis. DNA-binding also enables HMGA2 to protect cancer cells from DNA-damaging agents. HMGA2 therefore is considered to be a prime drug target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 40 publications
8
34
0
Order By: Relevance
“…Furthermore, our recent biochemical assays had shown that at a moderate range of HMGA2:scDNA stoichiometries, SN38-induced TOP1cc formation was enhanced 2- to 3-fold. At high stoichiometries, however, HMGA2 negatively interfered with TOP1 supercoil relaxation and reduced TOP1cc formation (29). It is likely that this results from direct competition between HMGA2 and TOP1, as both proteins recognize plectonemic DNA segment crossings in scDNA (28, 44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our recent biochemical assays had shown that at a moderate range of HMGA2:scDNA stoichiometries, SN38-induced TOP1cc formation was enhanced 2- to 3-fold. At high stoichiometries, however, HMGA2 negatively interfered with TOP1 supercoil relaxation and reduced TOP1cc formation (29). It is likely that this results from direct competition between HMGA2 and TOP1, as both proteins recognize plectonemic DNA segment crossings in scDNA (28, 44).…”
Section: Resultsmentioning
confidence: 99%
“…This form of supercoil scrunching, as well as the replication fork chaperone function, requires the presence of AT-hook DNA-binding domains of HMGA2 (27, 28). Furthermore, our recent unbiased high-throughput compound screen in combination with biochemical assays pointed at a functional interaction between HMGA2 and human TOP1 (29). We therefore hypothesized that HMGA2, in addition to or in conjunction with its proposed scaffold forming function at HU-induced stalled forks, may be a cancer/stem cell-specific modulator of dynamic changes in chromatin structure involving DNA supercoiling that contributes to replication fork stability during replication stress.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies showed that HMGA2 formed unique higher order complexes with scDNA in vitro and that within these ternary complexes, HMGA2 juxtaposes DNA segments into closer proximity to each other (Peter et al , ; Zhao et al , ). These results, in conjunction with the observed protective effect of HMGA2 against the catalytic inhibitor Merb, led us to investigate whether HMGA2 could catalytically activate TOP2A leading to more efficient supercoil relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Indicated amounts of Etop (Sigma) diluted in DMSO were incubated with 100 ng of supercoiled Renilla reporter plasmid (Peter et al , ) in a buffer containing 10 m m Tris/HCl, pH 7.9, 50 m m KCl, 50 m m NaCl, 5 m m MgCl 2 , 0.1 m m EDTA, 1 m m ATP, 15 µg·mL −1 BSA. The DNA supercoil relaxation reactions were initiated by adding 4.5 U of human recombinant TOP2A (Affymetrix, Santa Clara, CA, USA) to each sample.…”
Section: Methodsmentioning
confidence: 99%
“…The Dov-induced decrease in BER factors (MPG, APE-1, FEN1, PARP1, XRCC1) is anticipated to attenuate single-strand BER functions and enhance the occurrence of lethal dsDNA breaks (Davidson et al, 2013;Woodhouse et al, 2008). Another way of Dov to initiate DNA damage may involve HMGA2, which has recently been shown to augment topoisomerase I activity in a ternary complex with DNA and antagonize the topoisomerase I poison irinotecan/SN-38 (Peter et al, 2016). Attenuated HMGA2 expression may negatively affect topoisomerase I functions in GB.…”
Section: Discussionmentioning
confidence: 99%